Intermediate Actions to Improve the Business Scale of Bondo Bakery, a Micro Bakery Enterprise in Padang - Putra, Aronal Arief; Rahmi, Elfi; Yulia, Vitania; Sandra, Afriani (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Intermediate initiatives were launched to enhance the business scale of Bondo Bakery. This involved assessing the current conditions of the bakery, which led to several actionable options for improving its market position. Upgrades to facilities were made, along with training focused on baking for premium quality, production of affordable price of animal product-rich variants, bakery photography, and role-playing in baking classes. These actions resulted in the acquisition of standard equipment for kneading and preparation, improved the ability to produce high-quality bakery items, diversified the product offerings, created appealing visuals for social media advertising, and developed skills for conducting baking classes. In conclusion, the implemented actions are significant in increasing the bakery's business scale.